The Affection in Between : From Common Sense to Sensing in Common. - Flakne, April (Series in Continental Thought Ser., 2022)
"Drawing on phenomenology and everyday affective encounters of grieving, befriending, rearing, and bonding, Flakne warns against the disorientation and division implicit in what we think we mean by common sense. Instead, she invites us to relearn sensing together as key to an inevitable ethics of interembodiment"--